(untitled) (Revista Torreón Universitario, 2022)
A protocol for the prevention of COVID-19 was established to maintain the continuity of the external dosimetry service, which is applied to both laboratory personnel and customers. The evolution of the dosimetry service at the national level between 2019 and 2020 was compared in terms of the number of institutions attended and the number of users, as well as a possible increase in the personal dose equivalent. The COVID-19 pandemic generated a decrease in the number of institutions served in the last quarters evaluated, but not in the number of dosimeters read by the service. There was an increase of 1, 1 times in the average personal equivalent dose in 2020 concerning 2019, without exceeding the dose restrictions. There was no absence of LAF-RAM technical personnel, therefore, the dosimetry service was maintained without interruptions, considering the adopted protocol to be adequate.